2003
DOI: 10.1177/001440290306900407
|View full text |Cite
|
Sign up to set email alerts
|

Strategy Acquisition and Maintenance of Gifted and Nongifted Young Children

Abstract: Young childrens strategy acquisition and maintenance were examined by comparing the recall, clustering, and study behaviors of children of different ages and intelligences. Three groups were included in the study: 5-year-old gifted children, 5-year-old nongifted children, and 7-year-old nongifted children. All were observed and measured on 5 consecutive days, with training on strategy use provided on the third day. Several differences among groups were found, generally favoring the gifted children in terms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 16 publications
2
16
0
3
Order By: Relevance
“…Finally, two independent measures of adaptivity showed an increase in the adaptivity of children's strategy choices as a function of intelligence. The current study, which examined the contribution of intelligence to all four parameters of strategy competence at once in the context of a numerosity judgment task, confirms the results from earlier studies that addressed only one or some of these parameters in other domains such as simple arithmetic (Geary & Brown, 1991), memory, (Cho & Ahn, 2003;Scruggs & Mastropieri, 1988), and reasoning (Muir-Broaddus, 1995). Thus, the current study adds to the growing body of evidence suggesting that intelligence plays an important role in children's strategy selection and execution.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Finally, two independent measures of adaptivity showed an increase in the adaptivity of children's strategy choices as a function of intelligence. The current study, which examined the contribution of intelligence to all four parameters of strategy competence at once in the context of a numerosity judgment task, confirms the results from earlier studies that addressed only one or some of these parameters in other domains such as simple arithmetic (Geary & Brown, 1991), memory, (Cho & Ahn, 2003;Scruggs & Mastropieri, 1988), and reasoning (Muir-Broaddus, 1995). Thus, the current study adds to the growing body of evidence suggesting that intelligence plays an important role in children's strategy selection and execution.…”
Section: Discussionsupporting
confidence: 86%
“…First, we expected that the number of children that would demonstrate a strategy repertoire consisting of the addition and subtraction strategies would be positively related to the intelligence level. This prediction was based on two sets of findings: (a) the observation that high-intelligence children not only possess a broader strategy repertoire but also use more sophisticated strategies compared with their peers of lower intelligence (e.g., Cho & Ahn, 2003;Jausovec, 1991;Montague, 1991;Scruggs & Mastropieri, 1988;Siegler & Kotovsky, 1986) and (b) the observation that high-intelligence children have an increased propensity for insight (Davidson & Sternberg, 1984;Sternberg & Davidson, 1995) that makes them more prone to apply the sophisticated subtraction strategy from the onset of the study. Second, given that high-intelligence children apply the more sophisticated strategies in their repertoire more frequently than children of lower intelligence (Geary & Brown, 1991;Muir-Broaddus, 1995), we predicted an intelligence-related increase in the percentage of trials on which the subtraction strategy would be used.…”
Section: Experimental Task and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings contrast a vast body of research that has supported the use of Learning Strategies for students within the United States (Cho & Ahn, 2003;Robbins et al, 2004;Tait & Entwhistle, 1996;Vrugt & Oort, 2008). Some prior research examining multi-national samples has also indicated similar findings that Learning Strategies may not be universally effective for students from all countries (Chiu et al, 2007;Ghiasvand, 2010).…”
Section: Discussionmentioning
confidence: 64%
“…또한 성취수준이 뛰어난 영재학생들의 경우 다양한 학습 전략을 활용하는 것으로 보고된 바 있어 (김유미, 류성림, 2010;Zimmerman & Martinez-Pons, 1990) (양수민, 이귀숙, 2012;DeCharms, 1984;Leondari & Gialamas, 2002;Schunk, 1983;Shen & Pedulla, 2000;Vallerand et al, 1994;Zimmerman, Bandura, & Martinez-Pons, 1992 (구영수, 양연숙, 2013;문병상, 2000;조현철, 유수창, 2011;Cho & Ahn, 2003;Vandestoep, Pintrich, & Fagerlin, 1996;Yunus, Sulaiman, & Embi, 2013;Zimmerman & Martinez-Pons, 1990)을 뒷받침해 준다.…”
Section: 선행연구 고찰unclassified